Stable Reference Gene Selection for RT-qPCR Analysis in Synechococcus elongatus PCC 7942 under Abiotic Stresses. - Luo, Xiao; Li, Jiaxing; Chang, Tianliang; He, Hongyan; Zhao, Yi; Yang, Xue; Zhao, Yuwei; Xu, Yao (BioMed Research International, 2019)
Synechococcus elongatus PCC 7942 (S. elongatus PCC 7942) is a model cyanobacteria species for circadian clock mechanism studies. It has also been widely used as a bioreactor to produce biofuels and other metabolic products. Quantitative real-time PCR (qPCR) technology is the most commonly used method for studying the expression of specific genes, in which the relative expression level of target genes is calibrated by stably expressed internal reference genes. In this work, we examined the expression of nine candidate reference genes in time-course samples of S. elongatus PCC 7942 under no treatment (control), NaCl-stress conditions, H2O2-stress conditions, and high light-stress conditions. Based on the qPCR amplification parameters, the stability ranking of these candidate reference genes was established by three statistical software programs, geNorm, NormFinder, and BestKeeper. Considering all the stress conditions or high light stress alone, the results showed that the combination of prs and secA was the best choice for the double reference gene calibration method by qPCR. The combination of secA and ppc, rimM and rnpA, rnpA, and ilvD was most stable under no treatment, NaCl-stress conditions, and H2O2-stress conditions, respectively. rimM was stable under only special conditions and should be carefully chosen. 16S and rnpB were not suitable as internal reference genes for S. elongatus PCC 7942 qPCR experiments under all experimental conditions. To validate the above results, a cyanobacterial core clock gene, kaiC, was used to evaluate the actual performance of the optimized reference genes by qPCR, as well as the worst reference genes under different stress conditions. The results indicated that the best reference gene yielded more accurate calibration results for qPCR experiments carried out in S. elongatus PCC 7942 time-course samples.